Navigasi Psikologis dalam Pendidikan: Mengoptimalkan Efektivitas Belajar Berbasis Tahap Perkembangan dan Batasan Usia - Rizki Ni’matul Khasanah; Abdul Khobir; Alfiyatun Nur Fadhilah; Najwa Nafi’ah Zahra; M. Adham Adil Santoso (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2026)
This study aims to provide the benefits of a psychological approach in education through a learning adjustment strategy based on the developmental stage and age limits of students. The study used a library method with a qualitative descriptive-analytical approach through a review of educational psychology literature, cognitive development theory, national education regulations, and various relevant scientific journals. The results of the study indicate that learning effectiveness is greatly influenced by the alignment between material, teaching methods, and students' psychological readiness. Piaget's cognitive development theory indicates that elementary school-aged children are at the concrete operational stage, thus requiring contextual learning, the use of real-life media, and active interaction in the learning process. This study also found that age limits in the education system have an important function as a means of synchronizing students' biological, emotional, social, and intellectual readiness with learning targets. Through the "Psychological Navigation" model, this study offers a strategic framework for educators to create adaptive, humanistic learning that is oriented towards optimal student development. The implications of this study emphasize that teachers need to understand the individual characteristics of students so that the educational process does not only focus on academic achievement, but also supports the psychological well-being and character formation of students as a whole.